Characteristics of Self Compacting Concrete (SCC) by the Silica Fume as Portland Cement Substitute - Herliati Rahman; Puput Dwi Rahayu (Al-Kimia, 2021)
Self-compacting concrete (SCC) is a type of concrete that can flow by itself and can self-compact without using a compactor such as a vibrator. This study aims to observe the effect of cement substitution with silica fume on the compressive strength of concrete. The researchers expect a compressive strength of Self Compacting Concrete up to 500 kg/cm2, although silica fume substituted some portland cement. In order to reduce water use while maintaining the slump flow value of 60±2 cm, a superplasticizer was added at the fixed composition of 1.2% (w/w). The experimental design of silica fume as a cement substitute with a variation of 0%, 5%, 10%, and 15% (w/w). The concrete compressive strength test is carried out under the ASTM C234 standard, while the slump flow value refers to the ASTM C494 standard and the British Standard 5075. Although there was no compressive strength of 500 kg/m2 for all types of cement obtained, it shows that the highest compressive strength of SCC concrete was in the type of OPC cement at 28 days of age.